Artificial Intelligence (AI) for Low-Code and No-Code Development: Making Non-Developers Developers in 2024 - Kacheru, Goutham; Arthan, Nagaraju; Bajjuru, Rohit (PT FORMOSA CENDEKIA GLOBAL, 2025)
Low-code and no-code development platforms are here to transform the software development landscape by allowing even non-technical users build applications without the need of their advanced programming skills. Artificial Intelligence (AI) is the most crucial player in this evolution; reinvigorating these platforms with intelligent automation, device responsive templates and user-friendly interfaces (2024). Users can design, build, and deploy applications easily with AI-powered features (e.g., Natural Language Processing (NLP), drag-and-drop functionality to-design application & code-generation tools). Democratization of Application Development These innovations democratize application development, thereby allowing businesses to innovate faster, lessen the reliance on professional developers, and meet the surging demand for digital solutions. In this paper, we look at how AI-assisted low-code and no-code platforms are changing the way new apps are being developed, empowering non-developers to participate in software creation and accelerating automation of app development. It also presents the challenges and future aspects that we have to deal with in order to use AI on these platforms, as well as their future role of building a bridge between technical expertise and creative problem-solving.